Finland : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper reviews economic developments in Finland during 1990-95. The paper discusses the domestic economy, public finances, money and credit, and the balance of payments. It reports on the robustness of various inflation indicators, providing background to the process of establishing a monetary policy framework under a floating exchange rate. The paper also reviews possible structural causes for high unemployment and discusses reform proposals. Macroeconomic shocks that triggered the recession are analyzed. The role of financial factors in the transmission of those shocks economy-wide is also discussed.